Occurrence of DBPs in Drinking Water of European Regions for Epidemiology Studies. Issue 10 (1st October 2016) - Krasner, Stuart W.; Kostopoulou, Maria; Toledano, Mireille B.; Wright, John; Patelarou, Evridiki; Kogevinas, Manolis; Villanueva, Cristina M.; Carrasco‐Turigas, Glòria; Marina, Loreto Santa; Fernández‐Somoano, Ana; Ballester, Ferran; Tardon, Adonina; et al.
Abstract : A three‐year study was conducted on the occurrence of disinfection by‐products (DBPs)—trihalomethanes (THMs), haloacetic acids (HAAs), and haloacetonitriles—in drinking water of regions of Europe where epidemiology studies were being carried out. Thirteen systems in six countries (i.e., Italy, France, Greece, Lithuania, Spain, United Kingdom) were sampled. Typically chlorinated DBPs dominated. However, in most of Catalonia (Spain) and in Heraklion (Greece), brominated DBPs dominated. The degree of bromine incorporation into the DBP classes was in general similar among them. This is important, as brominated DBPs are a greater health concern. In parts of Catalonia, the reported levels of tribromoacetic acid were higher than in other parts of the world. In some regions, the levels of HAAs tended to be peaked in concentration in a different time period than when the levels of THMs peaked. In most epidemiology studies, THMs are used as a surrogate for other halogenated DBPs. This study provides exposure assessment information for epidemiology studies.